The Basic Political and Structural Problems in the Workings of Local Governments in Hungary - Pálné Kovács, Ilona (Discussion Papers, 1992)
The paper introduces the new established local government system in Hungary. The process, the values followed by the legislators showed which kinds of factors used to have an impact during the systemic changes and why the chosen local government model is fighting many malfunctions like fragmented, inefficient public services, financing problems, lack of integration, low performance in development policy etc. The paper tries to emphasise the path dependency in shaping territorial governance in a form of eliminating the almost always strong county governments and in the reluctance toward association of municipalities. Although the sand glass model of public power having strong bottom and top and lacking strong meso differs completely from the past as regards the power setting among levels but is similarly centralised. The original aim to strengthen the bottom is failed since the fragmented small municipalities were not able to fulfil the delegated tasks and what is the real paradox they even did not contribute to improving the local democracy and accessibility and quality of local basic services. The author’s conclusion is that the system of local governance needs general reform.